Diagnostic evaluation of enzyme activity related to steroid metabolism by mass spectrometry-based steroid profiling - Choi, M.H.; Chung, B.C. (Korean Society for Mass Spectrometry, 2014)
Gas chromatography-mass spectrometry (GC-MS) methods have been used extensively in clinical steroid analyses. Evaluating the metabolic ratios of precursors to products by accurate quantification of individual steroid levels in biological samples can reveal the activities of enzymes associated with steroid metabolism. This review article discusses the impact of GCMS- based steroid profiling on our understanding of the biochemical role of steroids and their metabolic enzymes in hormonedependent diseases, such as congenital adrenal hyperplasia (CAH), cortisol-mediated hypertension, apparent mineralocorticoid excess (AME), male-pattern baldness, and breast and thyroid cancers. Steroid profiling is a comprehensive analytical technique that can be applied whenever the highest specificity is required and may be a reasonable initial diagnostic approach.